Static pressure and dynamic impact characteristics of filled jointed rock after frozen-thaw cycle damage - Chai, Shaobo; Liu, Huan; Song, Lang; Li, Xianpeng; Fu, Xiaodong; Zhou, Yongqiang (Frontiers in Ecology and Evolution, 2023)
In the construction project, rock mass is often destroyed from the joint plane, and the jointed rock mass is easy to be eroded by freeze-thaw environment. Therefore, the damage mechanical properties of filled jointed rock mass under freeze-thaw action are very important for construction disaster prevention, engineering safety evaluation and reinforcement. In order to research the effect of the freeze-thaw cycle on the mechanical deterioration properties and damage characteristics of filled jointed rocks, prefabricated filled jointed rock samples are tested with different numbers of freeze-thaw cycles under the temperature range of -20℃~20℃. Then the wave velocity test, static compression test and SHPB impact test are conducted on the rock samples after freeze-thaw. Based on the test results, the change regularity of wave velocity degradation, static compression mechanical properties and dynamic compression mechanical properties of filled jointed rocks under the effect of freeze-thaw cycles were analyzed. The results show that the wave velocity, static compressive strength and dynamic compressive strength of the filled jointed rocks all show a downtrend with the increase of the number of freeze-thaw cycles, and each parameter is positively correlated with the strength of the filling materials. Among them, the decrease in the wave velocity of the rock sample after 30 freeze-thaw cycles is greater than 30%, and the strength loss of the static peak compressive strength exceeds half of its initial strength. The static peak strain rises exponentially with the increase of the number of freeze-thaw cycles while the dynamic peak strain does not show a clear trend. The dynamic peak strain is about 1/10 to 1/5 of the static peak strain. Under the same freeze-thaw action, the lower the strength of filling material, the more serious the damage.